Histology, prevalence, and environmental sources for pulmonary silicates depositions in domestic and wild animals. Issue 2 (March 2023) - Walker, Randall T.; Illanes, Oscar; Conan, Anne; Williams, Bruce H.; Hilchie, David; Bolfa, Pompei
The source and significance of pulmonary silicate crystals in animals and people are poorly understood. To estimate the prevalence and characterize the pulmonary crystalline material in animals from St. Kitts, tissue samples from dogs, horses, cattle, sheep, goats, pigs, chickens, mongooses, and monkeys were examined by light microscopy, scanning electron microscopy with energy-dispersive x-ray analysis (SEM/EDXA), and x-ray diffraction. Crystalline material was seen in 201 of 259 (77.6%) lung samples as perivascular and interstitial accumulations of heterogeneous crystalline particulate material, free or within macrophages (silicate-laden macrophages [SLMs]), mostly lacking evidence of chronic inflammation or fibrosis. The crystalline material was birefringent, basophilic on acid-fast, and composed of silicas on SEM/EDXA. Mongooses (100%) and monkeys (98%) had the highest prevalence of SLM, followed by cattle and chickens. Lesions were graded on a 3-point scale based on the histologic location and extent of silicates and SLM and were significantly more severe in mongooses (median = 3) than in monkeys (median = 2), dogs (median = 2), and chickens (median = 1). On EDXA, the crystalline material from lungs, air, and topsoil was composed of silicon, oxygen, aluminum, and iron, with a particulate matter size between 2.5 and 10 µm. We hypothesize Saharan dust, volcanic ash, topsoil, and rock quarry dust are potential sources of siliceous dust inhalation and SLM accumulations lacking chronic inflammation (silicosis); dust generation may be potentiated by road vehicle or wind suspension. Future investigations are warranted on the role of silicate inhalation and respiratory comorbidities in people, with monkeys, mongooses, or chickens serving as possible sentinels for exposure.